Safety and pharmacokinetics of bimagrumab in healthy older and obese adults with body composition changes in the older cohort. Issue 6 (2nd December 2020) - Rooks, Daniel; Petricoul, Olivier; Praestgaard, Jens; Bartlett, Michael; Laurent, Didier; Roubenoff, Ronenn
Abstract: Background: Bimagrumab prevents activity of myostatin and other negative regulators of skeletal muscle mass. This randomized double‐blind, placebo‐controlled study investigated safety, pharmacokinetics (PK), and pharmacodynamics of bimagrumab in healthy older and obese adults. Methods: A cohort of older adults (aged 70–85 years) received single intravenous infusions of bimagrumab 30 mg/kg ( n  = 6) or 3 mg/kg ( n  = 6) or placebo ( n  = 4) and was followed for 20 weeks. A second cohort of obese participants [body mass index (BMI) 30–45 kg/m 2, aged 18–65 years] received a single intravenous infusion of bimagrumab 30 mg/kg ( n  = 6) or placebo ( n  = 2) and was followed for 12 weeks. Outcomes included the safety, tolerability, and PK of bimagrumab, in both cohorts. Measures of pharmacodynamics were performed in the older adult cohort to evaluate the effects of bimagrumab on thigh muscle volume (TMV), total lean body mass (LBM), total fat body mass, and muscle strength. Results: All 24 randomized participants completed the study. The older adults had a mean (±SD) age of 74.5 ± 3.4 years and BMI of 26.5 ± 3.5 kg/m 2 . The obese participants had a mean (±SD) age of 40.4 ± 11.8 years, weight of 98.0 ± 11.3 kg, and BMI of 34.3 ± 3.9 kg/m 2 . Adverse events in both cohorts were mostly mild. In older adults, most commonly reported adverse events were upper respiratory tract infection, rash, and diarrhoea (each 3/16, 19%). Obese participants reported muscle spasms and rash (both 5/8, 63%) most often. Non‐linearity was observed in the PK concentration profiles of both cohorts due to target‐mediated drug disposition. Bimagrumab 3 and 30 mg/kg increased mean (±SD) TMV (Week 4: 5.3 ± 1.8% and 6.1 ± 2.2%, vs. placebo: 0.5 ± 2.1%, both P  ≤ 0.02) and LBM (Week 4: 6.0 ± 3.2%, P  = 0.03 and 2.4 ± 2.2%, vs. placebo: 0.1 ± 2.4%), which were maintained longer with higher dose level, while total fat body mass (Week 4: −2.7 ± 2.9% and −1.6 ± 3.0%, vs. placebo: −2.3 ± 3.2%) decreased from baseline in older adults, with no change in muscle strength. Conclusions: Bimagrumab was safe and well tolerated and demonstrated similar PK in older and obese adults. A single dose of bimagrumab rapidly increased TMV and LBM and decreased body adiposity in older adults. Muscle hypertrophy and fat loss were sustained with extended drug exposure.